ORGANIZATIONAL AND ECONOMIC ASPECTS OF THE ASSESSMENT OF STOCKS OF THE INTEGRATED TRADE ORGANIZATIONS - M. Sh. Ragimov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In article prerequisites of formation of the integrated trade organizations which cornerstone processes of deepening of specialization and cooperation of business activity are reveal. Possibilities of development of perspective odds of cooperation – distribution networks are considered. Methodical approaches to stockpile management of trade organizations are offered.